Homestay services in Kundasang area, Ranau, Sabah - Irwin Gandi (2015)
The increasing number of tourists that come to Kundasang was encouraging the villagers to join the homestay program. However, the activities that available around Kundasang have not improve since the program was launched. The main objective of this study is to identify the current status of homestay services in Kundasang. The study covers socio-demographic, tourist profile, and motive tourist to visit Kundasang homestay. The data for this research was collected by using open – ended questionnaire where 150 respondents had participated. The data was analyzed using the descriptive analysis. The result shows, the main reason of tourists that come to Kundasang are for rest and relaxation (23%) and barbeque activities as the preferences with mean of 3.0. As the conclusion, homestay owner just provide accommodation but less on the activities.
Project paper (B.For.Sc.) - Universiti Putra Malaysia, 2015.